Coronavirus: Nursing students' knowledge and risk perception of clinical practice during the pandemic - Ogechi Helen Abazie; Margaret Ihunanya Okwuikpo; Aderonke Julienne Adetunji; Chigozie Ihuoma Nweke (Kashan University of Medical Sciences, 2021)
Background: The attendance of nursing students in clinical settings is an inherent element of the nursing education, and it is the same even with the coronavirus disease 2019 (COVID-19) pandemic. Globally, more than 260 nurses have been killed by the COVID-19 disease and the number is still increasing. Objective: The study assessed nursing students' perception of clinical practice amidst coronavirus pandemic in southwest Nigeria. Methods: This is a cross-sectional study that utilized a multistage sampling method to select 300 respondents from the selected nursing institution in southwest Nigeria. The questionnaire is made up of three sections namely, sociodemographic variables, knowledge of COVID-19, and students' perception of clinical practice. Data were collected with Google Form and analyzed using descriptive and inferential statistics. Result: The mean age of the respondents was 22.16 ± 3.11 years and the mean year exposed to clinical practice was 2.73 ± 0.91 years. Majority (71%) had good knowledge of coronavirus, with mean ± standard deviation (SD) 16.16 ± 1.84, while 57.7% had a positive perception of clinical practice during coronavirus pandemic, with a mean ± SD of 3.62 ± 1.22. There was no significant difference between knowledge and perception of clinical practice post coronavirus pandemic, P = 0.088. There is a significant relationship between nursing students' perception of clinical practice with coronavirus and nursing institution (P = 0.001) and level of study (P = 0.001). Conclusion: The study showed that nursing students were willing to continue with their clinical practice even with coronavirus patients in the wards.